The Influence Of Leadership Style And Organizational Culture On Employee Performance At PT Bank BRI Muara Enim Branch - Nasution, Putri Utami Adauyah; Ermeila, Sri; Mario, Asma (Journal of Management, Economic, and Accounting, 2025)
This study aims to analyze the impact of leadership style and organizational culture on employee performance at PT Bank BRI Muara Enim Branch. The research employs a quantitative methodology, using questionnaires to collect data from 60 participants. The data collected were then analyzed using multiple linear regression. The findings of this study reveal that leadership style and organizational culture have a positive and significant influence on employee performance, both collectively and individually. These findings emphasize that strong leadership and a supportive organizational culture are essential for optimizing employee performance, particularly in the banking sector.